Ventilatory abnormalities in patients with cystic fibrosis undergoing the submaximal treadmill exercise test - Parazzi P.L.F. (2015)
© 2015 Parazzi et al.;licensee BioMed Central.Background: Exercise has been studied as a prognostic marker for patients with cystic fibrosis (CF), as well as a tool for improving their quality of life and analyzing lung disease. In this context, the aim of the present study was to evaluate and compare variables of lung functioning. Our data included: (i) volumetric capnography (VCAP) parameters: expiratory minute volume (VE), volume of exhaled carbon dioxide (VCO2), VE/VCO2, ratio of dead space to tidal volume (VD/VT), and end-tidal carbon dioxide (PetCO2); (ii) spirometry parameters: forced vital capacity (FVC), percent forced expiratory volume in the first second of the FVC (FEV1%), and FEV1/FVC%; and (iii) cardiorespiratory parameters: heart rate (HR), respiratory rate, oxygen saturation (SpO2), and Borg scale rating at rest and during exercise. The subjects comprised children, adolescents, and young adults aged 6-25 years with CF (CF group [CFG]) and without CF (control group [CG]). Methods: This was a clinical, prospective, controlled study involving 128 male and female patients (64 with CF) of a university hospital. All patients underwent treadmill exercise tests and provided informed consent after study approval by the institutional ethics committee. Linear regression, Kruskal-Wallis test, and Mann-Whitney test were performed to compare the CFG and CG. The α value was set at 0.05. Results: Patients in the CFG showed significantly different VCAP values and spirometry variables throughout the exercise test. Before, during, and after exercise, several variables were different between the two groups; statistically significant differences were seen in the spirometry parameters, SpO2, HR, VCO2, VE/VCO2, PetCO2, and Borg scale rating. VCAP variables changed at each time point analyzed during the exercise test in both groups. Conclusion: VCAP can be used to analyze ventilatory parameters during exercise. All cardiorespiratory, spirometry, and VCAP variables differed between patients in the CFG and CG before, during, and after exercise.